2011
DOI: 10.1002/aenm.201100007
|View full text |Cite
|
Sign up to set email alerts
|

In Situ X‐Ray Study of Drying‐Temperature Influence on the Structural Evolution of Bulk‐Heterojunction Polymer–Fullerene Solar Cells Processed by Doctor‐Blading

Abstract: Organic bulk heterojunction (BHJ) solar cells comprising conjugated polymers (as electron donor) and fullerene derivatives (as electron acceptor) deposited from solution make low cost photovoltaic-energy conversion feasible. [ 1 , 2 ] The active layer of BHJ solar cells comprises an interpenetrating network of polymer and fullerene domains that forms during deposition and drying. The energy-conversion process involves the creation of excitons upon light absorption which are dissociated into free charges at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
106
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 26 publications
6
106
0
Order By: Relevance
“…11,13 This can be challenging to investigate, as optical and X-ray scattering techniques previously developed to investigate film formation probe mainly the bulk and surface of the drying film, rather than its buried interface. [48][49][50][51][52][53][54][55] We have recently shown that thin film deposition at the solid-liquid interface, solvent vapour annealing and ligand exchange in colloidal quantum dot solids can be monitored using a quartz crystal microbalance with dissipation (QCM-D) capability. [56][57][58] QCM-D measures the change of frequency (∆f) and dissipation (∆D) at the surface of the microbalance in relation to mass deposition or loss and changes in the viscoelastic properties of the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 10 adsorbed mass, respectively.…”
Section: P3ht Thin Film Formationmentioning
confidence: 99%
“…11,13 This can be challenging to investigate, as optical and X-ray scattering techniques previously developed to investigate film formation probe mainly the bulk and surface of the drying film, rather than its buried interface. [48][49][50][51][52][53][54][55] We have recently shown that thin film deposition at the solid-liquid interface, solvent vapour annealing and ligand exchange in colloidal quantum dot solids can be monitored using a quartz crystal microbalance with dissipation (QCM-D) capability. [56][57][58] QCM-D measures the change of frequency (∆f) and dissipation (∆D) at the surface of the microbalance in relation to mass deposition or loss and changes in the viscoelastic properties of the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 10 adsorbed mass, respectively.…”
Section: P3ht Thin Film Formationmentioning
confidence: 99%
“…In situ X-ray diffraction has been previously used to provide insight to a variety of solution deposition processes, for example, the formation of OSCs films by drop casting, the formation of the photoactive layer in organic photovoltaics using spin coating and knife coating, the film formation of dip-coated nanoparticles and the formation of microstructures of collagen [31][32][33][34][35][36] . We have combined high-speed in situ microbeam grazing incidence wide-angle X-ray scattering (mGIWAXS) with high-speed in situ polarized optical microscopy (POM) to investigate the growth sequence of TIPS-pentacene polymorphs during solution shearing 28 .…”
mentioning
confidence: 99%
“…It was found for bulk heterojunctions of poly(3-hexyl)thiophene and [6,6]-phenyl-C61-butyric acid methyl ester (P3HT/PCBM) that the nanomorphology, phase separation, and crystallinity could be controlled by drying temperature through reduced molecular kinetics. 7 The effect of the P3HT:PCBM blend ratio on structural evolution of a drying doctor-bladed film indicated a strong molecular interaction between the two compounds, inhibiting P3HT p-p packing at a large excess of PCBM. 8 At an excess of P3HT it was found that crystallization of PCBM is inhibited long past the solubility limit.…”
Section: Introductionmentioning
confidence: 99%
“…Of relevance, though, are the recent intensive studies by Schmidt-Hansberg et al of the drying process of polymer solar cell active layer solutions, in a knifecoating setup (''doctor-blading''). [7][8][9] In these studies, X-ray diffraction of the drying film is measured in grazing incidence, while simultaneously monitoring the film thickness with a visiblelight reflectometer. It was found for bulk heterojunctions of poly(3-hexyl)thiophene and [6,6]-phenyl-C61-butyric acid methyl ester (P3HT/PCBM) that the nanomorphology, phase separation, and crystallinity could be controlled by drying temperature through reduced molecular kinetics.…”
Section: Introductionmentioning
confidence: 99%